Perm cinema journalism in new media - A.A. Sidyakina; A.F. Stabrovskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper is devoted to the peculiarities of Perm film journalism in the context of innovative trends of the industry. Laying a special emphasis on global changes in the media sphere associated with the development of the Internet and convergent journalism, we have focused on the potential of multimedia publications on cinema in the new media, identified relevant genre forms (guide, longread, special project about cinema), and noted an increasing role of the network of amateur critics. The review of Internet publications that publish materials about cinema is accompanied by the analysis of socio-cultural factors that stimulate the interest of the media in the sphere of cinema and contribute to the formation of the film critical segment of the Perm media field. Among the conditions for the intensification of the film-making process in the city, the most significant, according to the results of the research, are the activities of the Perm Cinematheque and the “Novyi Kurs” film production company, as well as media educational projects of the international documentary film festival “Flahertiana”. Taking into account the effective experience of the interaction between the university and cultural institutions, as well as emphasizing the importance of the art journalistic educational component, along with professional publications, student Internet newspapers that have earned the reputation of quality media and have become a basis for training in film journalism and film criticism have been considered.